Risk-taking behavior, the second-to-fourth digit ratio and psychological features in a sample of cavers - Sergio Rinella; Andrea Buscemi; Simona Massimino; Vincenzo Perciavalle; Marta Maria Tortorici; Daria Ghiunè Tomaselli; Valentina Perciavalle; Donatella Di Corrado; Marinella Coco (PeerJ, 2019)
Background The risk-taking behavior is largely modulated by the subject’s history, its lifestyles, by the characteristics of the situations with which it is compared, and also by the effects of prenatal androgens. Thus, the personality of the single person is a significant predictor of such way of acting. Methods The present study aimed to explore the relationship between Digit Ratio Measurement (2D:4D) and personality factors capable to be good predictors for choosing highly risky activities, such as caving. Furthermore, our purpose was to investigate whether 2D:4D ratio is related to cavers’ affective states and to assess the personological and emotional features of 34 healthy cavers, aged between 24 and 71 years (M = 39.70, SD = 9.81). Results Data analysis showed several significant correlations between 2D:4D and Deliberate Risk Taking (RTI) and Precautionary Behavior (RTI), confirming that 2D:4D is a reliable index able to predict risk-taking behaviors. Furthermore, data analysis showed that Conscientiousness and its sub-dimension Scrupulousness (BFQ-2) are recurrent among significant correlations; in particular, the latter reports negative correlations with many factors of POMS. Moreover, all participants seemed to have a good attitude to collaboration, in terms of goal-direct strategy, and an adequate management of negative affective states, useful to maintaining a good level of stress within the group. Finally, the BFQ-2 factor Openness to culture seemed to be a predominant feature in the cavers, and this feature could be considered as predictive in the choice of an activity, such as caving, which requires curiosity, perseverance and a great planning of cave exploration.